The investigation of an Open Distance and e-learning (ODeL) Centre at the University of Dar es salaam - Mgaiwa, Sophie Mynah (Curtin University, 2009)
Many higher education Institutions commit themselves to e-learning because they believe in its effectiveness as an alternative to traditional face to face methods of delivery, e-learning may to some extent increase enrolment and reduce training costs while allowing students the flexibility to attend classes at convenient times and places. University of Dar es salaam (UDSM) being the prime public university in Tanzania wants to adopt e-learning techniques in courses delivery; however the establishment of e-learning requires systematic planning, design, development and evaluation in order to achieve successful implementation. Therefore there is a need for the UDSM to address critical issues that might be faced by academics and the students in future.The aim of this study was to identify a culturally appropriate model inclusive of the most effective strategies and policies required for the establishment of an Open Distance e-learning (ODeL) centre at the University of Dar es salaam (UDSM). The study examined factors and conditions that reveal the importance of the development of an ODeL centre at the University of Dar es salaam, as well as analysing expertise (skills and knowledge) of the university’s academic and technical staff. It also examines existing models of similar centres from universities in both developed and developing countries. A mixed method was adopted where data was collected using a variety of tools: survey; interviews and content analysis.This study has indicated that the University of Dar es salaam can successfully develop an ODeL centre and implement e-learning if optimal capabilities of the selected media and technology are utilised effectively and efficiently. To support the development and delivery of e-learning a number of staff with a variety of skills and appropriate Information Communication Technology infrastructure are required. UDSM and other institutions wishing to participate in e-learning should review their educational policies and formulate strategies to ensure sustainability and quality of delivery.